PENGARUH JENIS PEREKAT DAN PENGERJAAN PERMUKAAN BIDANG REKAT TERHADAP KETEGUHAN GESER REKAT LAMINASI KAYU TERAP (Artocarpus elasticus Reinw. ex Blume) - Utomo, Riko Birau; Dayadi, Irvin (JURNAL ATOMIK, 2023)
This study aims to analyze the comparison of the adhesive shear strength value of the treatment used in the test sample, namely the difference in the type of adhesive with the difference in surface treatment of the adhesive plane. Analysis of variance (ANOVA) and LSD (Least Significant Difference) further test. The results of the analysis of variance showed that the effect of adhesive type (A) and surface treatment (B) on the adhesive shear strength of the laminate was very significant, while the interaction (AB) was not significant. Tests of physical and mechanical properties of laminated wood were carried out based on the JAS 234 - 2007 standard. The average moisture content of laminated timber was 11.59% and the average normal density was 0.329 g/cm³. The value of adhesive shear strength with A1 (epoxy) treatment of 69.79 kg/cm2 is greater than A2 (PVAc) of 63.98 kg/cm2 , while B3 (sanding) with the highest average of 72.86 kg/cm2 followed by B2 (planing) of 65.42 kg/cm2 and the lowest B1 (sawing) of 62.38 kg/cm2 . For the percentage of wood damage in the A1 (epoxy) treatment of 76.30% is higher than A2 (PVAc), while the treatment while B3 (sanding) with the highest average of 76.55% followed by B2 (planing) of 72.80% and the lowest B1 (sawing) of 71.00%, and has met the standard of JAS 234: 2007 (>54 kg/cm²).